Dormancy Breaking of Soursop (Annona muricata L.) Seeds Through Soaking in Onion Extract Hormones - Zebua, Erna Lydia Wati; Adelina, Rasmita; Nasution, Muhammad Nizar Hanafiah; Amnah, Rizky; Harahap, Sri Winaty; Siregar, Erin Alawiyah (International Journal of Natural Science Studies and Development (IJOSS), 2025)
Soursop is a perennial plant that has a hard seed coat that causes the seeds not to germinate immediately. This study aims to determine the effect of soaking shallot extract on soursop seed germination. This study was conducted from January to March 2025 at the Experimental Field of the Faculty of Agriculture, Graha Nusantara University. The research method used was an experimental method using a Randomized Block Design with one factor, namely the concentration of shallot extract hormones consisting of 5 levels, namely: K0 (control), K1 (20% extract), K2 (40% extract), K3 (60% extract), and K4 (80% extract). The observation parameters carried out were the percentage of total growth (%), germination rate, plant length (cm), number of leaves (strands), and root length (cm). The results showed that soaking shallot extract can help in soursop seed germination. The implementation of soaking in 20% extract showed a significantly different effect on plant length, number of leaves and root length.